THE EFFECT OF PRICE BEHAVIOUR ON INDONESIAN CPO EXPORT QUANTITY - Putri Budi Setyowati; Dessanty Fauziah Widayat; Budi Prihatminingtyas (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Unpredictable changes in supply and demand may cause the variation of price behavior. Crude Palm Oil (CPO) as Indonesian main export commodity has the highest risk of uncertainty price which is influenced by world price while it tends to fluctuate and become volatile in the given period. In order to increase CPO production, government has implemented biodiesel mandatory regulation namely B30 in 2019. It means that the use of diesel fuel with 20 percent of biofuel content. Besides that, government also applies zero tax policy to stimulate CPO producers in doing export. The objectives of this research are to analyze price volatility and its effect on export volume in the long term. Daily Indonesian CPO price since January 2010 to December 2017 was analyzed by Historical Volatility Method and Cointegration Test. This research shows that both domestic and world price of CPO tends to be high while domestic price is less volatile than world price. Furthermore, CPO’s price and export volume are cointegrated and have negative relation in the long term.